2019
DOI: 10.1038/s41598-019-51328-0
|View full text |Cite
|
Sign up to set email alerts
|

RNA-Seq analysis of ileocecal valve and peripheral blood from Holstein cattle infected with Mycobacterium avium subsp. paratuberculosis revealed dysregulation of the CXCL8/IL8 signaling pathway

Abstract: Paratuberculosis is chronic granulomatous enteritis of ruminants caused by Mycobacterium avium subsp. paratuberculosis (MAP). Whole RNA-sequencing (RNA-Seq) is a promising source of novel biomarkers for early MAP infection and disease progression in cattle. Since the blood transcriptome is widely used as a source of biomarkers, we analyzed whether it recapitulates, at least in part, the transcriptome of the ileocecal valve (ICV), the primary site of MAP colonization. Total RNA was prepared from peripheral bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
62
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(66 citation statements)
references
References 58 publications
3
62
1
Order By: Relevance
“…RNA-Seq data and genotypes. Samples from the animals included in this study were tested by ELISA for the detection of MAP-specific antibodies, qPCR for MAP DNA detection, bacteriological culture, and histopathological analysis, as previously described (Table 1) 18 . All control animals (N = 4) were negative for all the diagnostic tests.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…RNA-Seq data and genotypes. Samples from the animals included in this study were tested by ELISA for the detection of MAP-specific antibodies, qPCR for MAP DNA detection, bacteriological culture, and histopathological analysis, as previously described (Table 1) 18 . All control animals (N = 4) were negative for all the diagnostic tests.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, the infected cows had detectable lesions in gut tissues with distinct severity; focal/ multifocal (N = 6) or diffuse (N = 4). RNA-extraction from PB and ICV samples of the fourteen cows, RNA-Seq libraries preparation, and sequencing using an Illumina NextSeq500 sequencer were performed as previously described 18 . The raw reads were filtered by their length (minimum size 75 bp long) and percentage of ambiguous base N less than 10% using Prinseq-lite 0.20.4 25 .…”
Section: Resultsmentioning
confidence: 99%
“…SPARC, also known as osteonectin, is a matrix protein that binds collagen, and is required for the development of granuloma-like structures during chronic infections [ 57 ]. In our previous RNA-Seq study [ 39 ], the protein-protein interaction analysis revealed a COL1A2 centered network containing a COLI1A2-SPARC functional interaction. SPARC and COL1A2 were upregulated in the peripheral blood gene expression profiles from the cows with diffuse lesions which suggests that the expression of both proteins could lead to a bad prognosis in MAP-infected cows.…”
Section: Discussionmentioning
confidence: 99%
“…We previously identified several potential biomarkers for the diagnosis of MAP-infected animals [39]. Whole RNA-sequencing (RNA-Seq) was used to identify host genes differentially expressed in peripheral blood samples collected from animals with focal, or diffuse lesions in gut tissues vs. control animals without detected lesions nor bacterial load in gut tissues.…”
Section: Plos Onementioning
confidence: 99%
“…Thanks to recent advances in sequencing technology, RNA-seq based transcriptomic analyses with MAP infection have been performed in vitro and in vivo environments [22][23][24][25] . However, in vivo studies could not elucidate the initial stage of infection related to persistence, such as the immune response to the formation of granuloma, and in vitro studies could not represent the actual course of infection because the infection models were mainly based on single cell types, such as monocyte-derived macrophages (MDMs).…”
mentioning
confidence: 99%